Pemberdayaan Masyarakat melalui Perpustakaan Rumah Pintar “Baskara Cendikia” Desa Sekar Kecamatan Donorojo Kabupaten Pacitan Jawa Timur - Agustiani, Happy; Aorta, Dian Tias; Wahyuningsih, Diah (Lembaga Yasin AlSys, 2022)
The Smart House Library was formed to help community get access learning resources while at the same time give sufficient the needs of community in Sekar Village, Donorojo District, Pacitan Regency. Sekar Village located at the western end of Pacitan City. Sekar Village has a problem, there is minimal community facilities to develop knowledge and skills of its community. The Smart House Library